The relationship among the performance and the ACE I/D and ACTN3 R577X polymorphisms and some anthropometric factors in arm wrestlers - (:unkn) unknown (My University, 2023)
Sport genetics has become increasingly important in recent years. The concept of performance includes genetic and anthropometric factors. These factors have not been adequately examined when the current literature is examined. One of the aims of this study is to identify a possible interaction between the ACE ID and ACTN3 R577X polymorphisms and the sedentary, national arm wrestlers and amateur arm wrestlers, while another aim is to reveal some physical differences between the same persons. The research included 24 arm wrestlers who were members of the Turkish national team, 23 amateur arm wrestlers with club licenses, and 34 sedentary, all of the wrestlers participated voluntarily in the research. The genotype distribution of the ACE gene and ACTN gene and the statistical significance of the R, X, I, and D allele frequencies were compared by the Chi-Square test. The Anova one-way variance analysis was used to assess the difference among the palm circumference, wrist circumference, and forearm width among the groups, the significance was tested at p<.05 level. After the data was evaluated, significant differences were not found statistically in ACE nor ACTN3 polymorphisms in terms of the three groups (p>0.05). In addition, statistically significant differences were found in the palm, wrist, and forearm circumferences of the arm wrestlers who were the members of the Turkish national team compared especially to the sedentary (p<0.05). From the conducted research it was concluded that the success of the athlete in arm wrestling could not be directly explained by the ACE and ACTN3 genotypic characteristics. Another result revealed by this study was that the success of the athlete in arm wrestling was more related to palm, wrist, and forearm circumferences
Keywords: ACE ID; ACTN3 R577X; polymorphism; arm wrestling; anthropometry; palm circumference; width of the wrist; forearm circumference.